Neuroprotective effect of epidermal growth factor in experimental acrylamide neuropathy: an electrophysiological approach. Issue 2 (8th June 2017) - Perez‐Saad, H.; Subiros, N.; Berlanga, J.; Aldana, L.; Garcia del Barco, D.
Abstract: The neuroprotective effect of epidermal growth factor (EGF) has been documented in different contexts, but its potential benefits in peripheral neuropathies have been little studied. We investigated the neuroprotective action of EGF in experimental neuropathy induced by acrylamide (ACR). Mice and rats were treated chronically with acrylamide for 6 and 8 weeks, respectively. Concurrently they received EGF in daily doses of 1 and 5 mg/kg in mice and 3 mg/kg in rats, or saline (PBS). ACR severely affected the neurological score, the muscle strength, and the muscle potential M, in mice, as well as F‐waves (F‐Wii), sensory potentials (SPii), and apomorphine‐induced penile erection, in rats. EGF reduced the ACR effects in both species. A dose‐dependent effect of EGF was manifested in the proportion of diseased animals at the end of treatments, as well as in the reduction of M amplitude throughout the treatment. F‐Wii parameters were less protected by EGF than SP. The results show a protective effect of EGF in acrylamide‐induced neuropathy and support previous studies concerning the neuroprotective action of this peptide.